Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures